Pengaruh Pelatihan Dan Displin Kerja Terhadap Kepuasan Dan Kinerja Pegawai Dinas Perhubungan Kabupaten Merauke - Aldisa Arifudin (Musamus University, Merauke Papua Indonesia., 2018)
Human resources is the most important asset owned by an organization because The success of an organization is determined by humans. This study aims to determine to determine the effect of Training and Discipline against Job Satisfaction and Employee Performance of the Office of Transportation of Merauke Regency. This research uses quantitative method. This type of research is descriptive research is causal (causal), to determine the effect of a variable on other variables. In this study using path analysis model (path analysis) because among independent variables with dependent variable there is mediation that influence. This analysis is assisted with the help of SPSS 20.0 software. The result of test that have been done show that training has a positive and significant effect on satisfaction, work discipline has a positive and significant influence on satisfaction, training has a positive and significant influence on satisfaction employee performance, work discipline has a positive and significant influence on satisfaction employee performance, satisfaction has no effect on employee performance. Keywords: Training, Work Discipline, Satisfaction, Employee Performance